Penggunaan Pc Arc-Info Untuk Analisis Perbedaan Luas Bidang Peta Bersistem Proyeksi Tm-3° (Bpn) Dan Proyeksi UTM Dengan Transformasi Affine - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRAK The objective of this research is to evaluate the performance of the Affine Transformation in the PC Arc-Info to transform the projection system from TM 3° to UTM and to investigate the defferences between the areas (of land parcels) on the resulted UTM projection and those on the original TM 3° projection using Affine Transformation. The experimental results show that the area on TM 3° projection is numerically bigger then that on UTM projection.